Study of Flash Flood Evacuation in Nagari Andaleh, Batipuh Subdistrict, Tanah Datar Regency, West Sumatra Province West Sumatra: Kajian Evakuasi Bencana Banjir Bandang di Nagari Andaleh, Kecamatan Batipuh, Kabupaten Tanah Datar, Provinsi Sumatra Barat - Fauzan, Fauzan; Abdul Hakam; Bayu Martanto Adji (Universitas Lancang Kuning, 2025)
On Saturday, May 11, 2024, a flash flood struck parts of West Sumatra, including Nagari Andaleh. This disaster drew significant attention from the government and educational institutions, which responded by organizing the Disaster Community Service Program - Merdeka Belajar Kampus Merdeka (KKN-MBKM Kebencanaan) in Nagari Andaleh. As part of this program, students and Field Supervisors (DPL) carried out Community Service Activities Integrated with Student Activities (PkM-TKM), which included socialization about flash flood evacuation and the creation of an evacuation map. The activities began with drafting evacuation materials, validating, creating the map, and conducting field verification. Once the map was finalized, students and DPL, supported by Civil Engineering lecturers from UNAND, conducted socialization and training sessions on post-disaster impacts, including actions and evacuation directions that the Nagari Andaleh community should follow during a disaster. The high level of community participation during the discussions demonstrated strong enthusiasm for such positive initiatives. The outcomes of these activities included increased preparedness and knowledge among the Nagari Andaleh community regarding emergency responses to flash floods, enabling more effective evacuations during such events. Additionally, the flash flood evacuation map produced from this initiative serves as an important reference for both the community and local government of Nagari Andaleh to minimize disaster risks in the future.